2012
DOI: 10.1136/emermed-2012-201177
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in adults with a normal limited scaphoid MRI: a retrospective cohort study and follow-up questionnaire

Abstract: This study shows that limited extremity MRI can safely exclude clinically important injury. Significant symptoms do persist, however, for many patients with a normal MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…However, several patients with normal MRI had persistent symptoms. 96 A recent study using an examination protocol similar to the one described above 97 reported a small cost benefit for early MRI over conventional management with repeat radiography, but it also suggested a higher societal gain due to less unnecessary immobilization. Another recent study, adding limited MRI after normal follow-up radiographs 98 also showed similar costs to the standard protocol but reduced societal costs, as have other studies.…”
Section: Ultrasoundmentioning
confidence: 99%
“…However, several patients with normal MRI had persistent symptoms. 96 A recent study using an examination protocol similar to the one described above 97 reported a small cost benefit for early MRI over conventional management with repeat radiography, but it also suggested a higher societal gain due to less unnecessary immobilization. Another recent study, adding limited MRI after normal follow-up radiographs 98 also showed similar costs to the standard protocol but reduced societal costs, as have other studies.…”
Section: Ultrasoundmentioning
confidence: 99%